Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Challenging imperial feminism - Amos, Valerie; Parmar, Pratibha (Feminist Review, 1984)
Keywords: afro-féminisme; approches et analyses; cours; cycles supérieurs; discours dominant; fem9000; féminisme décolonial; féminismes noirs; genre; identités LGBTQIA2+; racisme; ressource en ligne; sexualité; système colonial; systèmes d'oppressions; thématiques